Studi Fenomenologi Dukungan Spiritual Keluarga pada Pasien Kanker - Arianti Arianti; Afifah Widyastuti; Sri Yona; Agung Waluyo (Universitas Faletehan, 2026)
Families play a crucial role in improving the health of patients with cancer. Spiritual support from their families empowers and helps them to believe that nothing is impossible if they believe in God. The purpose of this study was to explore the experiences of families providing spiritual support to patients with cancer at a hospital in Yogyakarta, Indonesia. This study employed a qualitative, phenomenological approach. Participants were selected using convenience and purposive sampling with 10 family members of the patients participating. The study was conducted from February 2025 to April 2025. Data collection involved in-depth interviews with participants, which were then analyzed using the six stages of thematic analysis outlined by Braun & Clarke. The results showed that families' experiences in providing spiritual support formed three themes: (1) family, friends, and the environment as sources of encouragement; (2) family members remaining supportive despite difficulties in worship; and (3) family concerns and fatigue in maintaining patient morale. This study concluded that families should continue to provide spiritual support to patients with cancers, despite experiencing emotional and physical exhaustion. Nurses should involve families in spiritual care while also supporting family caregivers.